6x+35+9x=15(x+4)-24

Simple and best practice solution for 6x+35+9x=15(x+4)-24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+35+9x=15(x+4)-24 equation:



6x+35+9x=15(x+4)-24
We move all terms to the left:
6x+35+9x-(15(x+4)-24)=0
We add all the numbers together, and all the variables
15x-(15(x+4)-24)+35=0
We calculate terms in parentheses: -(15(x+4)-24), so:
15(x+4)-24
We multiply parentheses
15x+60-24
We add all the numbers together, and all the variables
15x+36
Back to the equation:
-(15x+36)
We get rid of parentheses
15x-15x-36+35=0
We add all the numbers together, and all the variables
-1!=0
There is no solution for this equation

See similar equations:

| 5.5x+0.666x=37 | | 3xx1x=48 | | 8=a3−6 | | n÷31=2 | | 36-7p=-(p-5) | | -8x-14=7-2-4x+4x | | 7=p/3+5 | | (8x+6)-(7x=9) | | -110=13+3(4h-6)= | | 17−c=−7 | | 15y+22=52 | | 4n+2-4=-14 | | -2(x+6)=0,6x-14 | | x+83=163 | | 1=6o-5o | | n-3n=14-42 | | 16=7d-3d | | 17x-2+13x+2=180 | | 5=9w-8w | | x^2-2x+3=19 | | 19=2n=7(1=2n) | | -2y+3=1-3(2y+7) | | O=n-10n | | 7n-5(5n=6)=-40-8n | | 10-2(3-5x)=6x-2 | | 86=−6d+8 | | n+2=-141n | | (3x-10)*7=5 | | 48x^-2-6x=0 | | x+x(0.13)=335 | | -30=5-7w | | (3x-10)*7=0 |

Equations solver categories